Hybrid image processing approach for autonomous crack area detection and tracking using local digital image correlation results applied to single-fiber interfacial debonding. (July 2019) - Tabiai, Ilyass; Tkachev, Gleb; Diehl, Patrick; Frey, Steffen; Ertl, Thomas; Therriault, Daniel; Lévesque, Martin
Highlights: Full field local DIC measurements fail in the vicinity of cracks. Combining DIC measurements and raw images yields accurate crack area identification. Accurate crack area growth through the test is obtained for two single-fiber composites. Inter-facial debonding initiation appears to be independent of fiber-matrix bonding. Abstract: Local digital image correlation is a popular method for accurate full field displacement measurements. However, the technique struggles at autonomously tracking emerging and propagating cracks. We proposed a hybrid approach which utilizes image processing techniques in combination with local digital image correlation to autonomously monitor cracks in a mechanically loaded specimen. Our approach can extract and track crack surfaces and provide a volume-based visualization of the crack growth. This approach was applied to single-fiber composite experimental results with interfacial debonding from the literature. Results quantitatively show that strong interfacial fiber/matrix bonding leads to slower interfacial crack growth, delays interfacial crack growth in the matrix, requires higher loadings for crack growth and shows a specific crack path distinct from the one obtained for weak interfaces. The approach was also validated against a manual approach where a domain scientist extracts a crack using a polygon extraction tool. The method can be used on any local digital image correlation results involving damage observations.